Public Information Disclosure as a Determinant of Public Trust in Organizational Sustainability Initiatives - Indra Ardiyanto; Dinda Rakhma Fitriani (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to explore the role of public information transparency in building community trust toward organizational sustainability initiatives. With the increasing attention to sustainability practices, it is crucial for organizations to alter their information dissemination strategies. This qualitative research employed in-depth interviews with 10 participants, consisting of organizational representatives and community members. The analysis results indicate that a high level of information transparency positively impacts community trust. The findings also suggest that transparency in communication, both through sustainability reports and two-way dialogue, plays a significant role in reducing scepticism and enhancing community engagement. The study concludes that organizations prioritizing information transparency can establish stronger relationships with the public and improve the effectiveness of their sustainability initiatives. Therefore, it is recommended that organizations implement more transparent communication strategies to maximize public trust and support for their sustainability efforts.